DUOETHNOGRAPHY IN APPLIED LINGUISTICS QUALITATIVE RESEARCH - Werbińska, Dorota (Neofilolog, 2020)
The significance of duoethnography as an alternative qualitative method for investigating research in the humanities and social sciences has considerably increased in the last decade or so. Yet, despite its increasing popularity and the growth of duoethnographic studies in second and foreign language learning and teaching, duoethnography is still unknown to many applied linguists. In order to partially redress this gap, the aim of this article is to present duoethnography as a promising qualitative method for applied linguistics studies. The text outlines the basic tenets of duoethnography, discusses the scope of its research on language learning and teaching at the present time and describes innovations that duoethnography introduces to data collection, writing, presenting and interpreting research. The article concludes with a call for more duoethnographic studies in applied linguistics as they provide a welcome move towards greater methodological diversity. This, in turn, may contribute to our better understanding of the experience of language learning and teaching, and the identity of language learners and teachers, as well as generate new themes for research.